The Role of Family Physician in Case Finding, Referral, and Insurance Coverage in the Rural Areas - F Khayyati; M Esmaeil Motlagh; MJ Kabir; H Kazemeini; F gharibi; N Jafari (Tehran University of Medical Sciences, 2011)
Background: WHO suggest that family physician is the core in the world efforts for quality improvement, cost effectiveness, and equity in the health care systems. This study evaluates the impact of the program on accessibility of the services, case finding, patient referral, feedback process and insurance coverage in the rural health units. Methods: This study was quasi experimental. It compared the function of four health centers and eight health houses in the last three months of year 2004 with 2008. Data extracted from the available documents in the health units. Descriptive and analytical analysis was performed by using SPSS software. Results: The presence of physicians in health centers were 75 and 100 percent for 2004 and 2008 respectively, this rate for midwives were 50 and 100 percent for the same years respectively. The total referral cases to the hospitals were 2676, the feedback rate was recorded in 36% of the cases. In this case the follow up rate by physicians was 0% in 2004 and 3.17% in 2008.  Insurance coverage rate was 27% and 97% for 2004 and 2008 respectively within a meaningful P value range at 95% CI. ‍Conclusion: The findings of this study show that the family physician program has the positive impact on function of health units in terms of  availability of physicians and midwives and also insurance coverage at health centers in rural area, No impact on  patient follow up and case referral rate was detected.